(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Here’s some festival cheer for medium enterprises. Rather than an encouragement, this act of generosity is rather self-serving. I am referring to a recent notification by the Reserve Bank of India (RBI), which has allowed scheduled commercial banks to treat lending to medium enterprises as priority sector lending. This means, not only will more funds be available to medium enterprises it also means that these businesses can avail a subsidized rate of interest on these loans. Till the notification was issued, loans only to micro and small enterprises were classified as priority sector advances with a credit limit of Rs 5 crore. Medium enterprises were not provided this cover. The recent notification has not only brought medium enterprises under its ambit it has also revised the credit limit for micro and small enterprises to Rs 10 crore, which is also the credit limit for medium enterprises. (A medium enterprise is one where investment in plant and machinery is up to Rs 10 crore or Rs 5 crore in equipment) This new notification will be applicable to loans extended after November 13, 2013, and till the end of the current financial year. Regional rural banks have been excluded from including such advances in that category. In this study an attempt has been made to evaluate the priority sector lending of banks and the reality behind the minimum lending to priority sector by different banks.